Relationship between Environmental Leadership and Personality (Opennes, Conscientiousness, Extraversion, Agreebleness, Neuroticism) with a Corporate Environmental Performance - Emilkamayana Emilkamayana (IJEEM - Indonesian Journal of Environmental Education and Management, 2017)
This research aims to determine the relationship between environmental leadership and personality (opennes, conscientiousness, extraversion, agreebleness, neuroticism) with a corporate environmental performance on employees at PT Cahaya Anugerah Plantation Kutai Kartanegara. The method used is quantitative method with a correlation technique. The research was conducted from June to November 2016, with a total sample of 100 people. Analysis of Variance (ANOVA) showed association between environmental leadership and personality (Opennes, Conscientiousness, Extraversion, Agreebleness, Neuroticism) with a corporate environmental performance as calculated F value of 35,183 to the level of sig. of 0,000, where the figure is much lower than the level of sig. 0.05. These result indicate that environmental leadership and personality (opennes, conscientiousness, extraversion, agreebleness, neuroticism) did significantly affect the corporate environmental performance.